A study on factors contributes on organizational commitment among non-executive employee in SAJ Holdings Sdn. Bhd / Nurul Farhana Mohd. Zainy - Mohd. Zainy, Nurul Farhana (2014)
Globalization has not only helped the organization to look for efficient and effective employee but also made the expert, talented and accomplished employee retain in the organization. The role of Human Resource practices encourages employee engagement, organizational practices in retaining the employee and employee commitment is dominant. Organization is a social unit which people is structured and managed to meet a need to engage in collective goals. All organization has a management structure that determines the relationships between the different activities and assigns roles, responsibilities, and authority to carry out different tasks. To accomplish all the tasks the employee need to realize that commitment toward the organization will give them a good result for their work. For example, Petronas was a one of the biggest government linked company. To make sure all the talented and expert worker retain in the organization the top manager ask a human resource department prepare a good benefits to them such as a large amount of bonuses every year, child care, healthy card and so on. This kind of privilege will make employee happy to work with the organization and they also being loyal for a long term. The concept of organizational commitment has attracted considerable interest in an attempt to understand and clarify the intensity and stability of an employee’s dedication to the organization (Mesteret al.,2003). This researcher stated that, organizational commitment attract the employee to loyal and engaged with the organization. Furthermore, this study is more focuses about the factors that contribute to organizational commitment among non-executive employees in SAJ Hodings Sdn. Bhd. Organizational commitment also is the one of initiative that taken by management to keep employee leaving from the organization. Based on the topic, there are three factors that contribute to organizational commitment which are 1) communication, 2) compensation and benefits and 3) work environment. This study has chosen non-executive employee as respondent. Non-executive employee also can be known as middle worker and lower worker. Their scope of work is more in implementing agencies such as clerk, technician, crew and so on. Syarikat Air Johor Holdings Sdn. Bhd. has at 14 districts in Johor and Segamat district has been chosen. In this study, the respondent will be choosing from a different department and background.